The Interpretation Center of Historic Center of Lima - Deza de la Vega, Natalia Teresita (2020)
With the objective of knowing the situation of the Interpretation Center of the Historical Center of Lima, its context, problems and perspectives, a research was conducted in which 32 people were interviewed and a SWOT analysis based on daily experience and review of internal documents was carried out. This allowed gathering valuable information on the public perception of the Historical Center of Lima (CHL), its limitations, the opportunities and perspectives to improve the management of the Interpretation Center of the Historical Center of Lima and the fulfillment of its objectives, one of which is to reinforce the cultural identity of the population. Some of the recommendations, based on the results, are the presentation in english of the museum scripts, the improvement of the signage, the establishment of a fixed service schedule and the dissemination through social networks on their own platform